Travelers' perception towards budget hotel elements / Khaizie Sazimah Ahmad and Chatila @ Nurasyikin Jamal - Ahmad, Khaizie Sazimah; Jamal, Chatila @ Nurasyikin (Research Management Institute (RMI), 2012)
The budgets hotel sector is becoming increasingly popular even in advanced country such as Europe country and developing country such as China and India. Budget hotels' product concept is affordable not only for upper income and middle income that emphasize on value for money but also for low income travellers. This paper is aim to determine which attributes of Malacca's budget hotels that will influence travelers' decision and also to identify the significant factors that differentiate the choice of budget hotel between local and foreign travelers. We attempt to use the SERVQUAL and Fishbein's multi attribute model to give clear indication which of the attributes are most dominant in influencing travelers to make a decision to choose budget hotel. The SERVQUAL model is part of the satisfaction measurement techniques, while the Fishbein model is part of the attitude measurement techniques. A convenience sampling method was deemed appropriate for the purpose of this study. Malacca state becomes scope of this study based on the fact Malacca was most prominent tourism spot. While many researchers concentrate their studies on service quality measuring customer satisfaction on luxury hotels elements, very few studies emphasized on budget hotels sector especially in Malaysia. This study is expected to bring some practical implication by utilizing information obtained from the travelers to enhance a much more efficient marketing strategy in the budget hotel industry. The attributes that have been identified to be most crucial will became critical success factor to practitioners and can be focused by the hotels in their future decisions.